The experiences of family planning health professionals providing care to incarcerated patients: a qualitative study - Martha Paynter; Clare Heggie; Anja McLeod; Wendy V. Norman (BMC Pregnancy and Childbirth)
Abstract Background Although Canada completely decriminalized abortion in 1988, barriers persist, and people experiencing incarceration may face additional challenges. Family planning health professionals (FPHP) in the community may provide care to incarcerated people. This study is the first to examine their experiences and needs. Methods We used a community-based approach to this qualitative study and conducted interviews and focus groups with FPHP across Canada from multiple disciplines. Experts on the research team with lived experience of incarceration enhanced relevance of research questions and approaches. Results We spoke with thirty participants from eight provinces, including nurses, nurse practitioners, family medicine and obstetrics-gynecology physicians, and social workers. Analysis generated three themes: Managing Multiple Systems; The Prison in the Clinic; and Future Recommendations, and six subthemes, A Firewall of Secrecy, Logistical Hoop-Jumping, Surveillance by Correctional Officers, Health Professional Strategies, A Policy for Legitimacy and We Need This in Our Training. FPHP described commitment to providing incarcerated patients equivalent care to that provided to people in community, but faced challenges with communication, preserving patient dignity, privacy, confidentiality, and safety. Conclusion Findings indicate FPHP feel ethics and safety in jeopardy when caring for incarcerated patients. FPHP express needs for improved education about roles, and for supportive professional position statements or clinical workplace policies to buttress efforts at patient advocacy. No FPHP organization in Canada has a position on care of incarcerated pregnant people. Professional position statements and workplace policies could support confident care. FPHP training should include information about incarcerated peoples’ needs.